Hybrid α-Zirconium Phosphate/Polyaniline-Modified High-Density Polyethylene Composites with Enhanced Thermal Properties - Khanal, Santosh; Kandel, Mani Ram (Journal of Nepal Chemical Society, 2026)
Organic-inorganic hybrid nanofiller (PANI/α-ZrP) composed of polyaniline (PANI) and α-zirconium phosphate (α-ZrP) was synthesized via in-situ oxidative polymerization and characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM) and thermogravimetric analysis (TGA). The α-ZrP and hybrid PANI/α-ZrP were incorporated at different weight ratios (1%, 3%, and 5%) into high-density polyethylene (HDPE) by melt mixing. Thus formed composites were characterized by X-ray diffraction and thermogravimetric analysis (TGA). The XRD results suggested that HDPE composites have mainly exfoliated and/or partially intercalated structure. Moreover, the incorporation of the hybrid fillers slightly improves the thermal stability of HDPE. The PANI/α-ZrP hybrid combines the thermal stability and flame-retardant characteristics of α-ZrP with the mechanical flexibility and interfacial compatibility of PANI, enabling better dispersion and potential reinforcement in the polymer matrix.